Análise dos pressupostos metodológicos da utilização da planilha na educação : revisão de dissertações - Milão, Sílvia Monteiro (2015)
This work aims to explore the use of computers in the classroom environment, especially the use of spreadsheet. It also presents the results of a literature and qualitative review that has been conducted in six dissertations over the last four years, according to the site of Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), in which master students used the Spreadsheet in their didactic proposals for Elementary and High School classes. The goal is to understand, through research, the methodological processes used in academic research, with regard to computer use in classroom, particularly the use of spreadsheet of calculation. The methodology used for data analysis was the Discursive Textual Analysis (DTA) based on Moraes and Galiazzi (2001). The theoretical framework presents a view of the evolution of Information Technology in education and the contrast between theoretical lines, using the computer in the classroom and guidance on the use of Spreadsheet. As a result, the use of Spreadsheet as a tool of mathematics learning was considered not only viable and possible of being used in different contexts, but also with different teaching methodologies.